2023
DOI: 10.7554/elife.84983
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling based on structured surveys of Australian native possum excreta harboring Mycobacterium ulcerans predicts Buruli ulcer occurrence in humans

Abstract: Background: Buruli ulcer (BU) is a neglected tropical disease caused by infection of subcutaneous tissue with Mycobacterium ulcerans. BU is commonly reported across rural regions of Central and West Africa but has been increasing dramatically in temperate southeast Australia around the major metropolitan city of Melbourne, with most disease transmission occurring in the summer months. Previous research has shown that Australian native possums are reservoirs of M. ulcerans and that they shed the bacteria in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…As reported in other sequence enrichment studies, we observed decreasing genome sequence recovery with decreasing pathogen load, as indicated by increasing IS2404 Ct values (Figure 3A) 52 . Nevertheless, DNA sequence reads were obtained from five IS2404 positive mosquitoes and two IS2404 positive possum excreta specimens, the latter specimens collected as part of a large field survey of M. ulcerans in Australian native possum excreta in the region 53 . While DNA sequence reads were obtained across the length of the 5.6Mbp M. ulcerans reference chromosome, for all five mosquitoes and the two possum excreta specimens, only the excreta specimens (IS2404 Ct values <23) and three of the five mosquito DNA extracts (ID: 5675, Ct 32.62; ID: 226, Ct 33.47; ID: 819, Ct 31.20) yielded sufficient M. ulcerans reads for SNP-calling (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in other sequence enrichment studies, we observed decreasing genome sequence recovery with decreasing pathogen load, as indicated by increasing IS2404 Ct values (Figure 3A) 52 . Nevertheless, DNA sequence reads were obtained from five IS2404 positive mosquitoes and two IS2404 positive possum excreta specimens, the latter specimens collected as part of a large field survey of M. ulcerans in Australian native possum excreta in the region 53 . While DNA sequence reads were obtained across the length of the 5.6Mbp M. ulcerans reference chromosome, for all five mosquitoes and the two possum excreta specimens, only the excreta specimens (IS2404 Ct values <23) and three of the five mosquito DNA extracts (ID: 5675, Ct 32.62; ID: 226, Ct 33.47; ID: 819, Ct 31.20) yielded sufficient M. ulcerans reads for SNP-calling (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…These results also add to the growing body of evidence demonstrating the utility of pathogen genomics in specifically identifying the sources and transmission pathways of environmental pathogens and suggest that continued surveillance of M. ulcerans genotypes in mosquitoes and possums could be useful in guiding public health interventions that seek to control the spread of Buruli ulcer in the region. We are now exploring the use of genome sequence enrichment to dissect the genomic epidemiology from the perspective of environmental sources, in particular to track the spread of Buruli ulcer in Australian native possums across the region 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, recent studies have demonstrated that BU is a vector-borne zoonosis in Victoria, Australia, with mosquitoes and native possums as bacterial vectors and reservoirs, respectively [19, 3337]. While exact mechanisms of M. ulcerans transmission remain unclear, spatial clustering analysis has shown a striking overlap between clusters of human BU cases, M. ulcerans -harbouring mosquitoes and M. ulcerans -positive possum faeces in BU endemic areas of Victoria[33, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Common ringtail (CRT, Pseudocheirus peregrinus ) and to a lesser extent common brushtail (CBT, Trichosurus vulpecula ) possums, both of which are endemic and abundant in urban areas of Victoria, excrete large quantities of M. ulcerans in their faeces[19, 34], thus providing a potential source of environmental contamination for transmission to humans. Furthermore, the presence of M. ulcerans -positive possum excreta in a geographical area may be predictive of future human BU cases[37] possum excreta positivity in historically negative areas can predate the emergence of human BU cases by up to 31 months [39]. Faecal carriage of M. ulcerans in possums may be transient and can occur without accompanying clinical disease[36, 40].…”
Section: Introductionmentioning
confidence: 99%